2014
DOI: 10.1007/s00018-014-1709-x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for nuclear receptors in the pathogenesis of age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is the leading cause of vision loss in the elderly in the Western world. Over the last 30 years, our understanding of the pathogenesis of the disease has grown exponentially thanks to the results of countless epidemiology, genetic, histo-logical, and biochemical studies. This information, in turn, has led to the identification of multiple biologic pathways potentially involved in development and progression of AMD, including but not limited to inflammation, lipid and extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 194 publications
(202 reference statements)
1
48
0
Order By: Relevance
“…Either primary cell cultures or RPE cell lines (especially human ARPE19 cells) are used. We may wonder whether established cell lines still behave as in situ RPE cells, as they do not express the same cellular receptors [64,65]. …”
Section: Discussionmentioning
confidence: 99%
“…Either primary cell cultures or RPE cell lines (especially human ARPE19 cells) are used. We may wonder whether established cell lines still behave as in situ RPE cells, as they do not express the same cellular receptors [64,65]. …”
Section: Discussionmentioning
confidence: 99%
“…The main risk factor for developing AMD is increasing age, as prior studies have shown that the prevalence of AMD more than triples for individuals aged 75-85 as compared to those aged 43-54 4 . With the projected increase in the aging population in the world 3 , the impact of AMD on quality of life and medical cost is substantial 3, 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In neovascular or “wet” AMD, vision loss is induced by onset of neovascularization with resulting subretinal fluid and hemorrhage leading to fibrosis and loss of central vision. Significant advances have been made in the treatment of wet AMD, especially with the introduction of safe and effective anti-VEGF agents 5, 7 .…”
Section: Introductionmentioning
confidence: 99%
“…96 Noteworthy is that interest in studying NRs in AMD stems from the fact that the NR superfamily members are known to regulate many of these AMD-associated pathways in other diseases, such as cancer, atherosclerosis, and autoimmune disease. 5,6,8,22,24,96 The complexity of the disease can also be attributed to the tight interplay of cells, including the retinal pigment epithelial cells, photoreceptors, choroidal endothelial cells, and immune cells such as macrophages and microglia, the dysfunction of each of which contributes to AMD progression. Retinal pigment epithelial cell function and its role in drusen formation, and the secretion of angiogenic factors, are extensively studied, as the overall health of these cells is affected in all clinical subtypes of AMD.…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…8,24 Direct evidence comes from one study that examined the distribution of PPARγ in ocular samples from human dry and wet AMD patients and found increased immunoreactivity within the retina. 106 Changes in the expression levels of PPARγ in retinal pigment epithelial cells, as a function of age and disease, were not reported.…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%